BEING A RETURN MIGRANT – ADVANTAGE OR DISADVANTAGE IN LITHUANIAN LABOUR MARKET? - Žvalionytė, Dovilė (Politologija, 2015)
The paper explores how integration of return migrants into the labour market of their home country is influenced by the migration experience – does it give an advantage to returnees? Migration literature tends to focus on individual level factors such as human capital acquired abroad, to explain the success of the integration of returnees while somewhat neglecting the importance of the environment in their home country. This paper demonstrates that such structural factors as information asymmetry between a potential employer and a potential employee (in this case job-seeking returnee) as well as the perception of migration experience in the home country’s labour market should be also taken into account. The paper draws on an empirical study of the Lithuanian case. Consequently, the return migrants are defined as individuals who left Lithuania to reside permanently abroad for a period of at least one year after 1990 but were living permanently in Lithuania when the research was carried out. The main data sources of the research are three representative surveys carried out in 2013: a Lithuanian population survey (N = 1930), a survey of migrants who have returned to live in Lithuania (N = 804), and a survey of Lithuanian employers (N = 1000)52. The research revealed that almost all return migrants have acquired valuable knowledge and skills while abroad, which they expect to use in advancing their careers in Lithuania. As many as eight out of 10 migrants who have returned to live in Lithuania said that while abroad they improved some of their skills. Yet the returnees, in assessing whether the migration experience helped them in their employment in Lithuania, frequently stated that their emigration experience had no effect or even thought that it was a disadvantage and that their new knowledge and skills are undervalued in Lithuania. Correspondingly, over 60% of respondent employers indicated that migration experience would have no effect on their choice of employee, and one in ten employers stated that this would be a disadvantage. As could have been expected, there exists some heterogeneity in assessments of benefits of migration experience. For example, employers are relatively more positive about the experience gained abroad doing skilled work and less positive about doing unskilled work. Companies linked to other countries through their capital, market and business relations are also relatively more inclined to opt for returning migrants. However, it should be noted that more than half of employers do not view even skilled work abroad positively, and most of internationally oriented companies when hiring a new employee would choose one with work experience and education acquired in Lithuania rather than abroad. The paper argues that an important factor for ignoring the experience of returning migrants in the labour market is a somewhat unfavourable attitude towards return migrants and their migration experience present in the Lithuanian society and among employers. More than half of employers in Lithuania and almost half of the population of Lithuania agree with the statement that usually those who have failed abroad return to Lithuania. So, return is like a signal of failure, and employers who support this opinion are more likely to assess the migration experience as a disadvantage rather than an advantage. Thus, in order to better understand the processes of return migration and integration of returnees, attention must be paid to whether the home country’s labour market is returnee-friendly or unfriendly. Regardless of how much human capital return migrants bring from abroad, the successful integration of returnees is unlikely if their migration experience is not considered as an asset by the home country’s labour market. The returnee-unfriendly environment leads not only to the loss of potential benefits of human capital, but also to the unsuccessful reintegration of returnees and, eventually, to their repeat migration. Therefore, the Lithuanian migration policy which aims mainly at encouraging return migration, instead of focusing largely on the migrants themselves and their migration decisions, should devote much more attention to the integration process of returnees and include measures for making labour market more returnee-friendly.